2012
DOI: 10.1172/jci61888
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-specific dopaminergic deficits in a mouse model of Angelman syndrome

Abstract: Angelman syndrome (AS) is a neurodevelopmental disorder caused by maternal deletions or mutations of the ubiquitin ligase E3A (UBE3A) allele and characterized by minimal verbal communication, seizures, and disorders of voluntary movement. Previous studies have suggested that abnormal dopamine neurotransmission may underlie some of these deficits, but no effective treatment currently exists for the core features of AS. A clinical trial of levodopa (l-DOPA) in AS is ongoing, although the underlying rationale for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 58 publications
6
39
0
1
Order By: Relevance
“…Quinpirole elevated but did not lower BSR threshold in DBA mice, suggesting that this strain may have enhanced D2 autoreceptor and/or decreased postsynaptic D2 sensitivity, consistent with previous findings that D2-like receptor binding and mRNA expression are greater in the VTA and substantia nigra pars compacta and lower in the striatum of DBA compared with C57 mice (Ng et al, 1994;Cabib et al, 1998). In both strains, raclopride elevated thresholds and reduced MAX in a dose range similar to previous studies in C57 mice (Riday et al, 2012), and more potently in C57 than DBA mice, which is inconsistent with data on haloperidol-induced catalepsy (Kanes et al, 1993) and suppression of sucrose drinking by raclopride (Dym et al, 2009). Taken together, the differences in responses to quinpirole and raclopride suggest that, regarding reward-related behavior in both C57 and DBA strains, D2 receptors may contribute more than D1 receptors.…”
Section: Discussionsupporting
confidence: 90%
“…Quinpirole elevated but did not lower BSR threshold in DBA mice, suggesting that this strain may have enhanced D2 autoreceptor and/or decreased postsynaptic D2 sensitivity, consistent with previous findings that D2-like receptor binding and mRNA expression are greater in the VTA and substantia nigra pars compacta and lower in the striatum of DBA compared with C57 mice (Ng et al, 1994;Cabib et al, 1998). In both strains, raclopride elevated thresholds and reduced MAX in a dose range similar to previous studies in C57 mice (Riday et al, 2012), and more potently in C57 than DBA mice, which is inconsistent with data on haloperidol-induced catalepsy (Kanes et al, 1993) and suppression of sucrose drinking by raclopride (Dym et al, 2009). Taken together, the differences in responses to quinpirole and raclopride suggest that, regarding reward-related behavior in both C57 and DBA strains, D2 receptors may contribute more than D1 receptors.…”
Section: Discussionsupporting
confidence: 90%
“…Other candidate brain areas that could contribute to these locomotor deficits are the motor cortex and the nigrostriatal pathway, in which both UBE3A and αCaMKII are highly expressed. Notably, a recent study showed that AS mice exhibited behavioral deficits that correlated with abnormal dopamine signaling (47). Specifically, AS mice exhibited changes in dopamine release in both the mesolimbic and nigrostriatal pathways (47), whereas another study reported increased dopamine levels in the striatum, midbrain, and frontal cortex of AS mice (48).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study showed that AS mice exhibited behavioral deficits that correlated with abnormal dopamine signaling (47). Specifically, AS mice exhibited changes in dopamine release in both the mesolimbic and nigrostriatal pathways (47), whereas another study reported increased dopamine levels in the striatum, midbrain, and frontal cortex of AS mice (48). AS mice were also shown to have a reduced number of tyrosine hydroxylase-positive neurons in the substantia nigra (10).…”
Section: Discussionmentioning
confidence: 99%
“…Socially, Ube3a m-/p+ mice show reduced activity in social testing but not substantial social preference deficit [25,38]. Finally, Ube3a m-/p+ animals show pathway-specific misregulation of dopaminergic release, potentially contributing to both reward and motor phenotypes in these animals, and informing clinical trials for levodopa and the use of stimulants in patients with AS [44]. These animals are also prone to seizures depending on the background strain [35].…”
Section: As Mouse Modelsmentioning
confidence: 90%